Implementasi Gerakan Literasi Sekolah Sebagai Upaya Meningkatkan Kemampuan Literasi Peserta Didik Paket A di PKBM Budi Utama - Janah, Silvi Fatkul; Riyanto, Yatim (J+PLUS UNESA, 2024)
Non-Formal Education Institutions, one of which is PKBM Budi Utama, recently implemented a school literacy movement. This was carried out because of the implementation of the Independent Curriculum and based on the needs of students, especially Package A in terms of literacy. So, researchers want to examine the implementation of the Independent Curriculum through the School Literacy Movement in an effort to improve the literacy skills of Package A students at PKBM Budi Utama Surabaya, examine the supporting factors and inhibiting factors in the implementation of the Independent Curriculum through the School Literacy Movement in an effort to improve the literacy abilities of Package A students. . This research uses a qualitative approach. The data collection techniques used were interviews, observation and documentation. The results of this research indicate that the implementation of the literacy program is supported by a). Effective communication between facilitators or internally, facilitators and students; b). Non-human resources in the form of adequate space.